DECISION SUPPORT SYSTEM FOR SELECTION OF HOME OWNERSHIP LOANS (KPR) USING THE SMART METHOD - Candra Dewi Lestari; Mochzen Gito Resmi; Yudhi Raymond Ramadhan (RISTEC : Research in Information Systems and Technology, 2022)
The bank is a financial institution that has many activities, one of which is to serve housing loan (KPR) activities. As the human population increases, primary needs such as housing also increase. The existence of a Developer who will provide Home Ownership Loans is also needed for prospective buyers. With various offers, potential home buyers are difficult to make a decision. Therefore the authors through the Decision Support System (SPK) and the design of the Home Ownership Loan system provide a solution for prospective buyers in choosing the best mortgage with a Decision Support System using the SMART method. The SMART method is a multi-criteria decision-making technique based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important it is compared to other criteria